A whole body antibacterial quartz stone and preparation process

By using sepiolite to load butyl parabenzoate and modified sepiolite in artificial quartzite, combined with a composite adhesive of quartzite resin and epoxy resin, the problem that existing quartzite is prone to breed bacteria in humid environments is solved, and efficient overall antibacterial performance and durability are achieved.

CN118754506BActive Publication Date: 2025-04-25JIANGXI RISTON IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410742612.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-04-25
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

The existing artificial quartz stone is prone to breed bacteria in contact with food or in humid environments, and the antibacterial components of the existing antibacterial quartz stone sheets are unevenly dispersed and easily aged, affecting performance and antibacterial effects.

Method used

The formulations including quartz sand, quartz powder, composite resin, curing agent and antibacterial materials are adopted to improve its antibacterial properties in quartz stone materials through sepiolite, and the antibacterial durability of quartz stone is improved by modifying sepiolite. At the same time, quartz resin and epoxy resin are used as the adhesive to improve the dry bending strength of quartz material.

Benefits of technology

It achieves efficient and non-toxicity of the whole antibacterial quartz stone, easy to clean the surface, and has an antibacterial performance of 99.99%, exceeding the international standard by 10%. At the same time, it improves the antibacterial durability and heat water resistance of quartz stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754506B_ABST
    Figure CN118754506B_ABST
Patent Text Reader

Abstract

The present invention provides a full-body antibacterial quartz stone and a preparation process thereof, wherein the full-body antibacterial quartz stone comprises the following raw materials by mass: 50-55 parts of quartz sand, 28-32 parts of quartz powder, 10-15 parts of composite resin, 0.1-0.2 parts of curing agent, and 5-7 parts of antibacterial material. The present invention uses sepiolite to load butyl paraben, thereby improving its antibacterial performance in quartz material. At the same time, sepiolite is further modified to improve the antibacterial durability of quartz. The present invention provides a method of compounding quartz resin and epoxy resin as an adhesive to improve the dry bending strength of quartz material; under this condition, the hardness and aging resistance of quartz plate are simultaneously improved. The full-body antibacterial quartz stone of the present invention has the advantages of high efficiency, non-toxicity, easy surface cleaning, etc. Through special identification and detection, a non-toxic antibacterial quartz product is achieved, and the antibacterial performance reaches 99.99%, which exceeds the international standard by 10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz stone preparation, and in particular relates to a whole body antibacterial quartz stone and a preparation process. Background Art

[0002] Artificial high-end luxury stone texture, belonging to the building decoration interior wall, table craft material, refers to the artificial stone that imitates the unique texture and beauty of natural luxury stone through modern scientific and technological means. This material is designed to replicate the luxurious appearance of natural luxury stone (such as marble, jade, etc.), while providing more advantages in cost control, sustainability and design flexibility. It is an environmentally friendly, non-toxic, non-radiative, easy to clean, durable, and has passed the national JC / TSGS-2019 testing standard. New materials are widely used in countertops and interior decoration materials. Compared with natural luxury stone, artificial stone has a lower cost, allowing more consumers to afford high-end decorative materials. Colors, textures, and sizes can be customized according to customer requirements to meet diverse design needs. The exploitation of natural resources is reduced, and there is less waste in the production process. It can ensure the consistency of color and texture between batches, and is suitable for large-scale projects.

[0003] When artificial quartz is used in places that come into contact with food or in humid places, bacteria often grow on the surface. Ordinary artificial quartz has no effect on inhibiting or killing bacteria. Some existing antibacterial quartz slabs have antibacterial ingredients added to them, but there are still problems such as uneven dispersion of antibacterial ingredients and easy aging of quartz slabs, which affect the performance and antibacterial effect of the slabs. Therefore, there is an urgent need for a full-body antibacterial quartz to meet market demand. Summary of the invention

[0004] The purpose of the invention is to provide a whole body antibacterial quartz stone and a preparation process.

[0005] In order to achieve the above object, the present invention provides the following technical scheme: a whole body antibacterial quartz stone, comprising the following raw materials in parts by weight: 50-55 parts of quartz sand, 28-32 parts of quartz powder, 10-15 parts of composite resin, 0.1-0.2 parts of curing agent, and 5-7 parts of antibacterial material;

[0006] Wherein, the preparation method of the antibacterial material is:

[0007] (1) Mixing sepiolite in a mass ratio of 1:8-10 and hydrochloric acid in a mass fraction of 20-25%, stirring at 30-35° C. for 2-5 hours, removing the supernatant, washing with water until neutral, and drying to obtain acidified sepiolite;

[0008] (2) mixing acidified sepiolite, anhydrous ethanol and γ-aminopropyltriethoxysilane in a mass ratio of 10:60-80:0.2-0.3, heating to 60-70° C., stirring and refluxing for 4-6 hours, filtering and drying to obtain silane-modified sepiolite;

[0009] (3) Under a pressure of -0.1 to -0.095 MPa, the silane-modified sepiolite is heated to 80-85° C., and a 75-80° C. butyl p-hydroxybenzoate molten liquid and the silane-modified sepiolite are mixed until the butyl p-hydroxybenzoate molten liquid completely submerges the silane-modified sepiolite, and the mixture is allowed to stand for 15-20 minutes, centrifuged, and dried to obtain an antibacterial material.

[0010] Furthermore, the sepiolite has a particle size of 0.5-1 μm and a pore size of 10-50 nm.

[0011] Butyl parahydroxybenzoate has the advantages of high efficiency, non-toxicity, and easy surface cleaning. Because of its good antiseptic and antibacterial effects, it is used as a food-grade preservative and is also widely used in daily chemical products. However, the inventor found that the effect of using it on antibacterial quartz products is not ideal. Analysis shows that the dispersibility of butyl parahydroxybenzoate in the system is not ideal. The present invention uses sepiolite to load butyl parahydroxybenzoate, which improves its antibacterial performance in quartz materials. Analysis shows that through the adsorption of sepiolite, the dispersion of butyl parahydroxybenzoate in the system is enhanced, thereby improving the antibacterial property. Most of the uses of antibacterial plates are kitchen countertops, where food contact is relatively high and they need to be scrubbed frequently to ensure a long antibacterial durability, but the antibacterial durability of quartz is poor. The present invention further modifies sepiolite to improve the antibacterial durability of quartz. The analysis shows that the inner and outer surfaces of the acidified sepiolite contain more silanol groups. γ-aminopropyltriethoxysilane can react with the silanol groups on the inner and outer surfaces of the sepiolite, thereby making butyl parahydroxybenzoate more evenly dispersed and adsorbed, reducing the impact of the external environment on butyl parahydroxybenzoate and improving the antibacterial durability of the quartz. At the same time, the addition of antibacterial materials can improve the hot water resistance of the quartz. The analysis shows that the modified sepiolite has a porous structure, which can adjust the water absorption performance of the quartz plate and improve its hot water resistance.

[0012] The particle size of the quartz powder is 300-400 meshes, and the particle size of the quartz sand is 70-120 meshes.

[0013] Furthermore, the composite resin is a mixture of quartz resin and epoxy resin in a mass ratio of 2-3:1.

[0014] Furthermore, the preparation method of the epoxy resin is:

[0015] (1) In a helium atmosphere, epichlorohydrin, hydrogenated bisphenol A and glycerol are mixed and added to a reaction kettle, heated at 30-40° C. with stirring for 20-30 min, and a 30-33% potassium hydroxide aqueous solution is added, the temperature is raised to 42-45° C., and the reaction is carried out for 2-3 h; the reaction kettle is evacuated to 100 KPa, and a 30-33% potassium hydroxide aqueous solution is continuously added, the temperature is raised to 50-55° C., and the reaction is carried out for 4-5 h to obtain a bisphenol A epoxy resin;

[0016] (2) mixing γ-chloropropylmethyldiethoxysilane and phenyltriethoxysilane in a molar ratio of 1:1.5-2, adding the mixture to toluene, heating the mixture to 80-85° C., dropping hydrochloric acid having a mass concentration of 6-9%, reacting the mixture for 5-6 hours, cooling the mixture and removing the water layer to obtain an organosilicon modifier intermediate;

[0017] (2) Mix bisphenol A epoxy resin, organosilicon modifier intermediate and potassium hydroxide aqueous solution with a mass ratio of 5-6:1:8-9, heat to 70-75°C, react for 6-7h, cool to room temperature, separate and remove the water layer and epichlorohydrin, wash the organic solvent layer with distilled water until neutral, remove the organic solvent, and dry to obtain epoxy resin.

[0018] Furthermore, the molar ratio of epichlorohydrin to hydrogenated bisphenol A is 5-8:1.

[0019] Furthermore, the amount of glycerol used is 0.1-0.2% of the mass of hydrogenated bisphenol A.

[0020] Furthermore, the molar ratio of potassium hydroxide to hydrogenated bisphenol A in the potassium hydroxide aqueous solution added each time is 0.6-0.8:1.

[0021] Furthermore, the amount of hydrochloric acid used is 0.4-0.7 times the total mass of γ-chloropropylmethyldialkoxysilane and phenyltriethoxysilane.

[0022] Furthermore, the amount of toluene used is 8-10 times the mass of hydrochloric acid.

[0023] Furthermore, the curing agent is dibenzoyl peroxide.

[0024] Since the raw materials of the present invention contain quartz sand, quartz powder, and antibacterial material with bonding properties, the inventors found that the dry bending strength of the quartz material is not ideal when commercially available quartz resin is used as an adhesive. The present invention provides a quartz resin and an epoxy resin compounded as an adhesive to improve the dry bending strength of the quartz material. The analysis shows that by compounding the two resins, the dispersibility and compatibility of the resin in the system are improved, so that the quartz sand, quartz powder, and antibacterial material particles have better bonding, and the compounded resin can provide stronger cohesion, thereby improving the bending strength of the plate. The inventors found that under this condition, the hardness and aging resistance of the quartz plate are improved at the same time.

[0025] Furthermore, the quartz resin is model FX-883D quartz resin. Nantong Fangxin Chemical Co., Ltd.

[0026] Butyl p-hydroxybenzoate can be synthesized by reacting p-hydroxybenzoic acid with n-butanol in the presence of a catalyst. In the experiment, the amount of p-hydroxybenzoic acid was 0.05 mL, the amount of n-butanol was 3 times excess, and the theoretical yield was 9 g. NKC-9 and 167-B resins were used to catalyze the synthesis of butyl paraben.

[0027] The invention provides a preparation process of a full-body antibacterial quartz stone, comprising the following steps: adding an antibacterial material into a composite resin, stirring for 15-20 minutes, then adding a curing agent, stirring for 1-2 minutes, then adding the material into quartz sand and quartz powder, stirring for 3-4 minutes, pressing and curing a formed plate, and sequentially baking, scraping and polishing to obtain the full-body antibacterial quartz stone.

[0028] The pressing conditions are: vibration pressing and molding under vacuum conditions; pressure 80-100T, vibration frequency 40-50Hz, and vibration time 100-200s.

[0029] The curing conditions are: curing temperature 80-100°C, curing time 60-80min.

[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0031] 1. The present invention provides a whole body antibacterial quartz stone and preparation process, which has the advantages of high efficiency, non-toxicity, easy surface cleaning, etc. Through special identification and testing, the non-toxic antibacterial quartz stone product has an antibacterial performance of 99.99%, which exceeds the international standard by 10%. Using the preparation process of the present invention and adding various additives, a variety of quartz stones can be produced, see Figure 1-4 .

[0032] 2. The present invention uses sepiolite to load butyl paraben, thereby improving its antibacterial performance in quartz material. At the same time, sepiolite is further modified to improve the antibacterial durability of quartz. At the same time, the addition of antibacterial materials can improve the hot water resistance of quartz.

[0033] 3. The present invention provides a method of compounding quartz resin and epoxy resin as an adhesive, thereby improving the dry bending strength of the quartz material; under this condition, the hardness and aging resistance of the quartz plate are also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1-4 Schematic diagram of quartz stone prepared using the preparation process of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Some of the raw materials of the present invention were purchased from the following manufacturers:

[0037] Epichlorohydrin, Nanjing Kedite Trading Co., Ltd.;

[0038] Hydrogenated bisphenol A, Shanghai Fluoride Chemical Co., Ltd.;

[0039] γ-Chloropropylmethyldiethoxysilane, Qufu Chenguang Chemical Co., Ltd.;

[0040] Phenyltriethoxysilane, Guangzhou Shuangtao Chemical Co., Ltd.

[0041] Example 1

[0042] This embodiment provides a whole body antibacterial quartz stone, comprising the following raw materials in parts by weight: 52 parts of quartz sand, 30 parts of quartz powder, 12 parts of composite resin, 0.15 parts of curing agent, and 6 parts of antibacterial material;

[0043] Wherein, the preparation method of the antibacterial material is:

[0044] (1) Mixing sepiolite in a mass ratio of 1:9 and hydrochloric acid with a mass fraction of 22%, stirring at 32° C. for 4 h, removing the supernatant, washing with water until neutral, and drying to obtain acidified sepiolite;

[0045] (2) mixing acidified sepiolite, anhydrous ethanol and γ-aminopropyltriethoxysilane in a mass ratio of 10:70:0.24, heating to 65° C., stirring and refluxing for 5 h, filtering and drying to obtain silane-modified sepiolite;

[0046] (3) Under a pressure of -0.1 MPa, the silane-modified sepiolite is heated to 82°C, and a 77°C butyl parahydroxybenzoate molten liquid and the silane-modified sepiolite are mixed until the butyl parahydroxybenzoate molten liquid completely submerges the silane-modified sepiolite. The mixture is allowed to stand for 18 minutes, centrifuged, and dried to obtain an antibacterial material.

[0047] The particle size of the sepiolite is 0.5-1 μm, and the pore size is 10-50 nm. Neixiang County Hongyang Sepiolite Co., Ltd.

[0048] The particle size of the quartz powder is 300-400 meshes, and the particle size of the quartz sand is 70-120 meshes.

[0049] The composite resin is a mixture of quartz resin and epoxy resin in a mass ratio of 2.4:1.

[0050] The preparation method of the epoxy resin is:

[0051] (1) In a helium atmosphere, epichlorohydrin, hydrogenated bisphenol A and glycerol were mixed and added to a reactor, heated at 35° C. with stirring for 25 min, and a 32% potassium hydroxide aqueous solution was added, the temperature was raised to 44° C., and the reaction was carried out for 2.4 h; the reactor was evacuated to 100 KPa, and a 32% potassium hydroxide aqueous solution was continuously added, the temperature was raised to 52° C., and the reaction was carried out for 4.5 h to obtain a bisphenol A epoxy resin;

[0052] (2) Mixing γ-chloropropylmethyldiethoxysilane and phenyltriethoxysilane in a molar ratio of 1:1.8, adding the mixture to toluene, heating the mixture to 82° C., dropping 8% hydrochloric acid, reacting the mixture for 5.4 hours, cooling the mixture and removing the water layer to obtain an organosilicon modifier intermediate;

[0053] (2) Mix bisphenol A epoxy resin, an organosilicon modifier intermediate and a potassium hydroxide aqueous solution with a mass ratio of 5.4:1:8.6, raise the temperature to 72°C, react for 6.4 hours, cool to room temperature, separate and remove the water layer and epichlorohydrin, wash the organic solvent layer with distilled water until it is neutral, remove the organic solvent, and dry to obtain an epoxy resin.

[0054] The molar ratio of epichlorohydrin to hydrogenated bisphenol A is 7:1.

[0055] The amount of glycerol used is 0.15% of the mass of hydrogenated bisphenol A.

[0056] The molar ratio of potassium hydroxide to hydrogenated bisphenol A in the potassium hydroxide aqueous solution added each time is 0.7:1.

[0057] The amount of hydrochloric acid used is 0.5 times the total mass of γ-chloropropylmethyldialkoxysilane and phenyltriethoxysilane.

[0058] The amount of toluene used is 9 times the mass of hydrochloric acid.

[0059] The curing agent is dibenzoyl peroxide.

[0060] The quartz resin is model FX-883D quartz resin. Nantong Fangxin Chemical Co., Ltd.

[0061] The preparation process of the whole body antibacterial quartz stone comprises the following steps: adding the antibacterial material into the composite resin, stirring for 18 minutes, then adding the curing agent, stirring for 1.5 minutes, then adding the curing agent into the quartz sand and quartz powder, stirring for 3.5 minutes, pressing and curing the formed plate, and sequentially baking, scraping and polishing to obtain the whole body antibacterial quartz stone.

[0062] The pressing conditions are: vibration pressing under vacuum conditions; pressure 90T, vibration frequency 45Hz, and vibration time 150s.

[0063] The curing conditions are: curing temperature 90°C, curing time 70 minutes.

[0064] Example 2

[0065] This embodiment provides a whole body antibacterial quartz stone, comprising the following raw materials in parts by weight: 50 parts of quartz sand, 32 parts of quartz powder, 10 parts of composite resin, 0.2 parts of curing agent, and 5 parts of antibacterial material;

[0066] Wherein, the preparation method of the antibacterial material is:

[0067] (1) Mixing sepiolite with a mass ratio of 1:10 and hydrochloric acid with a mass fraction of 20%, stirring at 35° C. for 2 h, removing the supernatant, washing with water until neutral, and drying to obtain acidified sepiolite;

[0068] (2) mixing acidified sepiolite, anhydrous ethanol and γ-aminopropyltriethoxysilane in a mass ratio of 10:80:0.3, heating to 70° C., stirring and refluxing for 4 h, filtering and drying to obtain silane-modified sepiolite;

[0069] (3) Under a pressure of -0.095 MPa, the silane-modified sepiolite is heated to 85°C, and a 75°C butyl p-hydroxybenzoate molten liquid is mixed with the silane-modified sepiolite until the butyl p-hydroxybenzoate molten liquid completely submerges the silane-modified sepiolite. The mixture is allowed to stand for 20 minutes, centrifuged, and dried to obtain an antibacterial material.

[0070] The particle size of the sepiolite is 0.5-1 μm, and the pore size is 10-50 nm. Neixiang County Hongyang Sepiolite Co., Ltd.

[0071] The particle size of the quartz powder is 300-400 meshes, and the particle size of the quartz sand is 70-120 meshes.

[0072] The composite resin is a mixture of quartz resin and epoxy resin in a mass ratio of 2:1.

[0073] The preparation method of the epoxy resin is:

[0074] (1) In a helium atmosphere, epichlorohydrin, hydrogenated bisphenol A and glycerol were mixed and added to a reactor, heated at 40° C. with stirring for 20 min, and a 33% potassium hydroxide aqueous solution was added, the temperature was raised to 42° C., and the reaction was carried out for 3 h; the reactor was evacuated to 100 KPa, and a 30% potassium hydroxide aqueous solution was continuously added, the temperature was raised to 55° C., and the reaction was carried out for 4 h to obtain a bisphenol A epoxy resin;

[0075] (2) Mixing γ-chloropropylmethyldiethoxysilane and phenyltriethoxysilane in a molar ratio of 1:2, adding the mixture to toluene, heating the mixture to 80° C., dropping hydrochloric acid having a mass concentration of 9%, reacting the mixture for 5 h, cooling the mixture and removing the water layer to obtain an organosilicon modifier intermediate;

[0076] (2) Mix bisphenol A epoxy resin, organosilicon modifier intermediate and potassium hydroxide aqueous solution with a mass ratio of 6:1:8, heat to 70°C, react for 7 hours, cool to room temperature, separate and remove the water layer and epichlorohydrin, wash the organic solvent layer with distilled water until neutral, remove the organic solvent, and dry to obtain epoxy resin.

[0077] The molar ratio of epichlorohydrin to hydrogenated bisphenol A is 5:1.

[0078] The amount of glycerol used is 0.2% of the mass of hydrogenated bisphenol A.

[0079] The molar ratio of potassium hydroxide to hydrogenated bisphenol A in the potassium hydroxide aqueous solution added each time is 0.6:1.

[0080] The amount of hydrochloric acid used is 0.7 times the total mass of γ-chloropropylmethyldialkoxysilane and phenyltriethoxysilane.

[0081] The amount of toluene used is 8 times the mass of hydrochloric acid.

[0082] The curing agent is dibenzoyl peroxide.

[0083] The quartz resin is model FX-883D quartz resin. Nantong Fangxin Chemical Co., Ltd.

[0084] The preparation process of the whole body antibacterial quartz stone comprises the following steps: adding the antibacterial material into the composite resin, stirring for 20 minutes, then adding the curing agent, stirring for 2 minutes, then adding into the quartz sand and quartz powder, stirring for 3 minutes, pressing and curing the formed plate, and sequentially baking, scraping and polishing to obtain the whole body antibacterial quartz stone.

[0085] The pressing conditions are: vibration pressing under vacuum conditions; pressure 100T, vibration frequency 40Hz, and vibration time 200s.

[0086] The curing conditions are: curing temperature 80°C, curing time 80 minutes.

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 1 is that the preparation method of the antibacterial material is: under a pressure of -0.1 MPa, the sepiolite is heated to 82°C, and a 77°C butyl parahydroxybenzoate molten liquid is mixed with the sepiolite until the butyl parahydroxybenzoate molten liquid completely immerses the sepiolite, and the mixture is allowed to stand for 18 minutes, centrifuged, and dried to obtain the antibacterial material.

[0089] The particle size of the sepiolite is 0.5-1 μm, and the pore size is 10-50 nm.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 1 is that the particle size of the sepiolite is 0.15-2 μm, and the pore size is 100-200 nm. Neixiang County Hongyang Sepiolite Co., Ltd.

[0092] Comparative Example 3

[0093] The difference between this comparative example and Example 1 is that the composite resin is a mixture of quartz resin and epoxy resin in a mass ratio of 5:1.

[0094] Comparative Example 4

[0095] The difference between this comparative example and Example 1 is that the composite resin is a mixture of quartz resin and epoxy resin in a mass ratio of 1:1.

[0096] Comparative Example 5

[0097] The difference between this comparative example and Example 1 is that the epoxy resin is replaced by bisphenol A epoxy resin. Sigma-Aldrich (Shanghai) Trading Co., Ltd., Sigma-Aldrich, item number 31185.

[0098] Performance Testing

[0099] 1. Antibacterial property test: Referring to JC / T897-2014 Antibacterial property of antibacterial ceramic products, the antibacterial property and antibacterial durability of the quartz stones prepared in Examples 1-2 and Comparative Examples 1-5 were determined (the cleaning method during the use of the product was simulated, and the antibacterial property after multiple washing tests was tested). The results are shown in Table 1.

[0100] Table 1 Antibacterial test results

[0101]

[0102]

[0103]

[0104] 2. The quartz stones prepared in Examples 1-2 and Comparative Examples 1-5 were cut into plates with a length of 300 mm, a width of 150 mm, and a height of 20 mm, and the following performance tests were performed.

[0105] (1) Use a hardness tester to measure the Mohs hardness;

[0106] (2) Use a microcomputer-controlled electronic universal testing machine to test the dry bending strength;

[0107] (3) Hot water resistance test: After 100 hours in 80℃ water, if there are no cracks or bubbles, it is qualified; if there are cracks and / or bubbles, it is unqualified.

[0108] (4) Aging test: Light source: 1A (UVA340nm) lamp, irradiance 0.76w / m / nm at 340nm, blackboard temperature 60℃, condensation temperature 50℃, humidity not controlled. Exposure cycle: irradiation mode 4h, condensation mode 2h, rain for 12 minutes, 10 cycles, relative humidity not controlled. No cracks, no bubbles, qualified, cracks and / or bubbles, unqualified.

[0109] Table 2 Test results

[0110]

[0111] The results show that the quartz stone prepared in Examples 1-2 has good antibacterial properties and excellent physical and chemical properties. Comparative Examples 1-5 show that the comprehensive properties decrease to varying degrees when the preparation conditions are changed.

[0112] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A whole body antibacterial quartz stone, characterized in that: The raw materials include the following parts by weight: 50-55 parts of quartz sand, 28-32 parts of quartz powder, 10-15 parts of composite resin, 0.1-0.2 parts of curing agent, and 5-7 parts of antibacterial material; The preparation method of the antibacterial material is as follows: (1) mixing sepiolite with a mass ratio of 1:8-10 and hydrochloric acid with a mass fraction of 20-25%, stirring at 30-35°C for 2-5h, removing the supernatant, washing with water to neutrality, and drying to obtain acidified sepiolite; (2) mixing acidified sepiolite, anhydrous ethanol and γ-aminopropyltriethoxysilane with a mass ratio of 10:60-80:0.2-0.3, heating to 60-70°C, stirring; Stir and reflux for 4-6 hours, filter, and dry to obtain silane-modified sepiolite; (3) heat the silane-modified sepiolite to 80-85° C. under a pressure of -0.1 to -0.095 MPa, mix the 75-80° C. butyl p-hydroxybenzoate molten liquid and the silane-modified sepiolite until the butyl p-hydroxybenzoate molten liquid completely immerses the silane-modified sepiolite, let stand for 15-20 minutes, centrifuge, and dry to obtain an antibacterial material; The particle size of the sepiolite is 0.5-1 μm, and the pore size is 10-50 nm; the particle size of the quartz powder is 300-400 mesh; the composite resin is a compound of quartz resin and epoxy resin in a mass ratio of 2-3:1, and the quartz resin is a model FX-883D quartz resin; The preparation method of the epoxy resin is as follows: (1) in a helium atmosphere, epichlorohydrin, hydrogenated bisphenol A and propylene glycol are mixed, added to a reaction kettle, heated at 30-40° C. and stirred for 20-30 min, and a potassium hydroxide aqueous solution with a mass concentration of 30-33% is added, the temperature is raised to 42-45° C., and the reaction is carried out for 2-3 h; the reaction kettle is evacuated to 100 KPa, and a potassium hydroxide aqueous solution with a mass concentration of 30-33% is continuously added, the temperature is raised to 50-55° C., and the reaction is carried out for 4-5 h to obtain a bisphenol A epoxy resin; (2) a γ-chloropropylmethyldiethoxy Silane and phenyltriethoxysilane are mixed, added to toluene, heated to 80-85°C, hydrochloric acid with a mass concentration of 6-9% is added dropwise, the reaction is carried out for 5-6 hours, and the water layer is removed after cooling to obtain an organic silicon modifier intermediate; (3) bisphenol A epoxy resin, organic silicon modifier intermediate and potassium hydroxide aqueous solution with a mass ratio of 5-6:1:8-9 are mixed, the temperature is raised to 70-75°C, the reaction is carried out for 6-7 hours, the temperature is cooled to room temperature, the water layer and epichlorohydrin are separated and removed, the organic solvent layer is washed with distilled water until neutral, the organic solvent is removed, and the epoxy resin is obtained.

2. The whole body antibacterial quartz stone according to claim 1, characterized in that: The molar ratio of epichlorohydrin to hydrogenated bisphenol A is 5-8:

1.

3. The whole body antibacterial quartz stone according to claim 1, characterized in that: The amount of glycerol used is 0.1-0.2% of the mass of hydrogenated bisphenol A.

4. The whole body antibacterial quartz stone according to claim 1, characterized in that: The molar ratio of potassium hydroxide to hydrogenated bisphenol A in the potassium hydroxide aqueous solution added each time is 0.6-0.8:

1.

5. The whole body antibacterial quartz stone according to claim 1, characterized in that: The amount of hydrochloric acid with a mass concentration of 6-9% is 0.4-0.7 times the total mass of gamma-chloropropylmethyldialkoxysilane and phenyltriethoxysilane.

6. A process for preparing the whole body antibacterial quartz stone according to any one of claims 1 to 5, characterized in that: The following steps are involved: Add the antibacterial material to the composite resin, stir for 15-20 minutes, then add the curing agent, stir for 1-2 minutes, add it to the quartz sand and quartz powder, stir for 3-4 minutes, press and cure to form a plate, and then bake, scrape and polish it in turn to obtain the whole body antibacterial quartz stone.

7. The preparation process according to claim 6, characterized in that: The pressing conditions are: vibration pressing and molding under vacuum conditions; pressure 80-100T, vibration frequency 40-50Hz, and vibration time 100-200s.

8. The preparation process according to claim 6, characterized in that: The curing conditions are: curing temperature 80-100°C, curing time 60-80min.

Citation Information

Patent Citations

  • Organosilicon-modified epoxy resin, preparation method thereof and organosilicon-modified epoxy resin adhesive

    CN109851759A

  • Antibacterial, antiviral and mildew-proof quartzite table top and preparation method thereof

    CN111302705A

  • Antibacterial mildew-proof composite melamine impregnated paper and preparation method thereof

    CN117802830A